2010
DOI: 10.1002/jbmr.160
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-induced autophagy in osteocytes

Abstract: Glucocorticoid (GC) therapy is the most frequent cause of secondary osteoporosis. In this study we have demonstrated that GC treatment induced the development of autophagy, preserving osteocyte viability. GC treatment resulted in an increase in autophagy markers and the accumulation of autophagosome vacuoles in vitro and in vivo promoted the onset of the osteocyte autophagy, as determined by expression of autophagy markers in an animal model of GC-induced osteoporosis. An autophagy inhibitor reversed the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(139 citation statements)
references
References 28 publications
7
131
0
1
Order By: Relevance
“…The results of the present study suggest that a decline in osteocyte autophagy may also contribute to the adverse effects of age on the skeleton. Recent studies have provided evidence that glucocorticoids stimulate autophagy in the MLO-Y4 osteocytic cell line (51). Based on these studies, the increased endogenous glucocorticoid levels in aged mice might be expected to increase autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study suggest that a decline in osteocyte autophagy may also contribute to the adverse effects of age on the skeleton. Recent studies have provided evidence that glucocorticoids stimulate autophagy in the MLO-Y4 osteocytic cell line (51). Based on these studies, the increased endogenous glucocorticoid levels in aged mice might be expected to increase autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…61 Low-dose glucocorticoid treatment has also been shown to induce autophagy in osteocytes in response to increased oxidative stress caused by treatment, preserving the viability of these cells. [62][63][64] Studies indicate that autophagy also plays an important role in bone resorption by osteoclasts. 65 It has been reported that proteins involved in the autophagic pathway are important in the regulation of osteoclastogenesis, 66,67 indicating that this process participates both in bone formation and resorption.…”
Section: Role Of Autophagy In Bone Biologymentioning
confidence: 99%
“…Administration of GCs leads to a reduction in bone mineral density (BMD), decreased generation of osteoblasts and osteocytes and prolonged lifespan of osteoclasts, with fractures occurring in 30-50% of patients chronically treated with GCs (1). Recent studies have demonstrated that GCs can induce apoptosis and autophagy in osteocytes (4)(5)(6). The influence of GCs has been rarely reported on chondrocytes, which play a key role in skeletal development.…”
Section: Introductionmentioning
confidence: 99%